Development and characterization of a sustainable process for the implementation of lightweight ceramics. Issue 7 (1st April 2023) - Rubino, G.; Trovalusci, F.; Vesco, S.
Abstract: Addition of hollow particles and foamed core-shell structures was evaluated to reduce density of ceramic bodies used in the production of sanitary ware, in particular Vitreous-China. Different contents of foamed ceramic beads, glass bubbles or foamed glass beads were tested, ranging from 1.5 to 10 % wt. These strategies were designed to be readily applicable to a pre-existing industrial plant, leading to a final product that retains mechanical and aesthetical properties of traditional ceramic.Mechanical properties, shrinkage, water absorption, surface finishing, and weight reduction were evaluated on dried and fired simplified samples.A moderate reduction in mechanical properties was found, numerically dependent to the overall volume of voids introduced in ceramic bulk. In particular, ceramic with a content of 3% of glass bubbles featured a flexural strength at break of 35 MPa, out of standard requirement. The highest efficiency in weight reduction was achieved with the introduction of 1.5% of cave glass bubbles resulting in a reduction of 10% in weight of fired samples, a flexural strength at break of (41 ± 4) MPa, a total linear shrinkage of (10.1 ± 0.2) %, (0.5 ± 0.1) %, water absorption of 0.5 % wt, in accordance with regulatory standard requirements.Weight reduction improved sustainability in terms of environmental impact. LCA (Life Cycle Assessment) study was conducted on optimized ceramic body (glass bubbles at 1.5 %wt, and glass bubbles at 3% with comparative purposes), evaluating the production process from transportation of raw materials to distribution of goods overseas. LCA analysis was determined using impact categories of ReCiPe Midpoint (H), ReCiPe EndPoint (H/H), and cumulative energy demand (CED). The analysis showed an overall improvement of all the impact categories, with a reduction of CED of 10%, and a reduction of ReCiPe Endpoint of 15% for optimized sample.